2023
DOI: 10.3389/fonc.2023.1141191
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lipopolysaccharide-related genes are involved in the invasion and recurrence of prostate cancer and are related to immune escape based on bioinformatics analysis

Abstract: BackgroundThe composition of the tumor microbial microenvironment participates in the whole process of tumor disease. However, due to the limitations of the current technical level, the depth and breadth of the impact of microorganisms on tumors have not been fully recognized, especially in prostate cancer (PCa). Therefore, the purpose of this study is to explore the role and mechanism of the prostate microbiome in PCa based on bacterial lipopolysaccharide (LPS)-related genes by means of bioinformatics.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…This study has shown potent anti-tumorigenic efficacy pre-clinically and reports signals of immune modulatory changes from flow cytometry analysis in treatment-naïve patients with confirmed cancer, including prostate cancer [ 18 ]. It is fascinating how microorganisms in the prostate cancer microenvironment may use complex mechanisms and networks to regulate the occurrence and development of prostate cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has shown potent anti-tumorigenic efficacy pre-clinically and reports signals of immune modulatory changes from flow cytometry analysis in treatment-naïve patients with confirmed cancer, including prostate cancer [ 18 ]. It is fascinating how microorganisms in the prostate cancer microenvironment may use complex mechanisms and networks to regulate the occurrence and development of prostate cancer [ 19 ].…”
Section: Discussionmentioning
confidence: 99%